Self-assessment of acute mountain sickness in adolescents: a pilot study. - Imray, C; Kennedy, C; Pattinson, K; Brearey, S; Wright, A (2004)
OBJECTIVE: To perform a pilot study exploring the prevalence of acute mountain sickness (AMS) in adolescents on ascent to altitude and evaluating whether this age group is capable of self-assessment of AMS using the Lake Louise scoring system. METHODS: Twelve teenagers aged 15 to 18 years old (5 girls) traveled for 21 days between 2400 and 5500 m. Each member of the expedition completed a Lake Louise self-assessment questionnaire on a daily basis. Group leaders (nonmedical) were informed about any subject with a score of 3 or more. Appropriate treatments were then initiated. Detailed analysis of data was undertaken on return to the UK. RESULTS: There was 100% completion of 252 questionnaires. Eleven of the 12 subjects (91.7%) had symptom scores greater than or equal to 3, consistent with a diagnosis of AMS, on at least one day (range, 0-8). Symptoms of AMS were more common in the female group members (P = .041). CONCLUSIONS: AMS is a common problem among adolescents. There are increasing numbers of adolescents traveling to high altitudes, and there appears to be a lack of information about the prevalence of AMS in this age group. Motivated adolescents seemed capable of self-monitoring for AMS using the Lake Louise questionnaire. Combined with an appropriate ascent profile and support, we feel this approach may contribute to safety in the mountains and merits further study.